Distinguishing China's processing trade in the world input-output table and quantifying its effects. Issue 3 (3rd July 2019) - Chen, Quanrun; Zhu, Kunfu; Liu, Peng; Chen, Xiangyin; Tian, Kailan; Yang, Lianling; Yang, Cuihong
ABSTRACT: Distinguishing processing trade is crucial to national input-output table-based research on China's international trade. This paper further investigates the importance of distinguishing China's processing trade in multicountry input-output table-based studies. We focus on the bias in China's bilateral trade in value added caused by China's undistinguished processing trade. We construct a product-by-product world input-output table capturing China's processing trade based on the World Input-Output Database. Empirical studies show that, if China's processing trade is undistinguished, the profile of China's bilateral trade in value added would be seriously distorted; China's bilateral net trade in value added with some economies, such as Japan, Korea and Taiwan, would be significantly underestimated, while it would be significantly overestimated for some other economies, such as the United States. Distinguishing processing trade in multicountry input-output tables is also crucial when China's bilateral trade in value added is considered.